Clinical, biochemical and ultrasonic changes in the liver in small intestine enzymopathy in children - Uvarova, I O; Kamilova, A T; Aripov, A N (Klinicheskaia laboratornaia diagnostika, 2004)
We followed 70 patients, aged 1 to 11 years: 30 children had primary celiac enzymopathy (CE), the other had secondary fermentopathy represented by the celiac syndrome in 20 subjects and by the disaccharidase insufficiency syndrome (DIS) in another 30 subjects. Distinct disorders were registered in the liver and hepatobiliary system in children with enzymopathy variations of the small intestine (ESI). Despite a general identity of the clinical signs observed in ESI, the ultrasound signs of the fat hepatosis were more often the case in the celiac disease rather than in the celiac syndrome. The results should be considered in the rational diet- and drug therapy in children with the above pathology.